A Review of the Effectiveness Natural Pigment as Antidiabetic to Decrease the Significant Risk For COVID-19 Disease - Surya, Vincent Satya; Alexander; Sandra; Marpaung, Abdullah Muzi (Journal Akademik Universitas Swiss German, 2022)
Diabetes mellitus proved to be a significant risk factor for both COVID-19 infection and poor outcomes among these chronic health problems. Plants are a rich source of chemical components that could block carbohydrate digestion enzymes, and they can be utilized as therapeutic or functional foods. Natural pigments that have potential benefits, such as chlorophyll, anthocyanin as a part of flavonoid, and carotenoid. Chlorophylls are the most significant and widespread pigment molecules in nature, and they are required for photosynthesis to occur. Anthocyanins are the most important group of water-soluble pigments in plants, responsible for the red, purple, and blue colors of many fruits, vegetables, cereal grains, and flowers. Carotenoids, natural pigments found in an array of different foodstuffs, are the most abundant pigments present in the human diet. The most frequent method for determining a substance's antidiabetic potential is to assess the substance's hypoglycemic or antihyperglycemic.